ANALISIS PENDAPATAN USAHATANI PADI SAWAH DENGAN METODE SRI (System of Rice Intensification) DI DESA EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Mario Francisco Tamba; Evy Maharani; Susy Edwina (Universitas Lancang Kuning, 2017)
Paddy is one of main farming commodity since rice is one of main food in Indonesia. Innovation adoption about paddy farming was meaningful, because there were land conversion from food farming to industrial land or plantation. This study aimed to know about the adoption of farming technical was used by farmers, then aimed to know the efficiency of farming. This study took place in Empat Balai Village Kuok Sub-district Kampar Municipality. The results of this study showed there were differences about faming technical between faming technical with SRI and conventional faming technical that was used for a long time. The differences between SRI paddy farming and conventional farming were the amount of seeds per planted hole and the use of fertilizers. The amount of seeds on SRI method was only 1 seed per planted hole, meanwhile the use of fertilizers was more prioritize on using the organic materials i.e. golden snail, rice water, and brown sugar. On the other hand, there was an increasing of paddy production from SRI method which reached the production of 3.014,51 kg per ha. The increase of production caused the increase of total net income by SRI method Rp.14.953.667,01 per ha. RCR value of this farming was 1,76 per ha, which the value of RCR > 1 then this farming was profitable categorized.